ANALYSIS OF CIVIL SERVANT HUMAN RESOURCES DEVELOPMENT BASED ON COMPETENCE - Izmi, Izmi Hanif Firladi; Hermawati, Nuri (Universitas Airlangga, 2025)
The administration of the government sector and public services requires quality, competent and professional civil servant human resources to realize customer satisfaction in public services. This research is intended to determine the development of civil servant human resources through competencies that are carried out and regulated by the government in accordance with the theory of competence. As well as comparing with one of the countries that ranks well in providing public services, namely Canada. The results show that the development of civil servant human resources in Indonesia is in accordance with Charles E. Johnson's competency theory. In addition, the competence of civil servants in Canada is not much different from that in Indonesia. However, the low competence of civil servants in Indonesia requires the awareness of those concerned about their obligations to carry out their duties according to the duties and functions of their respective agencies.